Large increases in plasma fast skeletal muscle troponin I after whole-body eccentric exercises. Issue 8 (August 2020) - Chen, Trevor C.; Liu, Hung-Wen; Russell, Alan; Barthel, Benjamin L.; Tseng, Kuo-Wei; Huang, Min-Jyue; Chou, Tai-Yi; Nosaka, Kazunori
Abstract: Objectives: It has been reported that plasma fast skeletal muscle troponin I (fsTnI) but not slow skeletal muscle troponin I (ssTnI) increases after a bout of eccentric exercise of the elbow flexors. The present study compared the first and second bouts of whole-body eccentric exercises for changes in plasma fsTnI and ssTnI concentrations. Design: Observational study in an experimental group. Methods: Fifteen sedentary men (20–25 y) performed nine eccentric exercises targeting arm, leg and trunk muscles, and repeated them two weeks later. Blood samples were taken before and for five days following each bout, and plasma ssTnI and fsTnl concentrations were measured by enzyme-linked immunosorbent assays. Their changes were compared between bouts and their relationships to plasma CK activity and myoglobin concentrations were analysed. Results: Plasma fsTnI concentration increased after the first bout and peaked at 4 days post-exercise (2152–40, 295 ng/mL), but no significant increases were evident after the second bout. Plasma ssTnI concentration did not change significantly from the baseline (<0.08 ng/mL) after either bout. Peak plasma fsTnI concentration was significantly (p < 0.005) correlated with peak plasma CK activity (peak: 23, 238–207, 304 IU/L, r = 0.727) and myoglobin concentration (1047–3936 μg/L, r = 0.625) after the first bout. Conclusions: These results suggest that plasma TnI concentrations are more specific biomarker of muscle damage than plasma CK activity and myoglobin concentration. It seems that the whole-body eccentric exercises induced damage preferentially to fast-twitch muscle fibres, and increases in plasma CK activity and myoglobin concentration after eccentric exercise may reflect fast-twitch muscle fibre damage.